Research Priorities in Pediatric Asthma: Results of a Global Survey of Multiple Stakeholder Groups by the Pediatric Asthma in Real Life (PeARL) Think Tank - Mathioudakis, Alexander G; Custovic, Adnan; Deschildre, Antoine; Ducharme, Francine M; Kalayci, Omer; Murray, Clare; Garcia, Antonio Nieto; Phipatanakul, Wanda; Price, David; Sheikh, Aziz; Agache, Ioana; Bacharier, Leonard; et al. (The journal of allergy and clinical immunology. In practice, 2020)
BACKGROUND: Pediatric asthma remains a public health challenge with enormous impact worldwide. OBJECTIVE: The aim of this study was to identify and prioritize unmet clinical needs in pediatric asthma, which could be used to guide future research and policy activities. METHODS: We first identified unmet needs through an open-question survey administered to international experts in pediatric asthma who were members of the Pediatric Asthma in Real Life Think Tank. Prioritization of topics was then achieved through a second, extensive survey with global reach, of multiple stakeholders (leading experts, researchers, clinicians, patients, policy makers, and the pharmaceutical industry). Differences across responder groups were compared. RESULTS: A total of 57 unmet clinical need topics identified by international experts were prioritized by 412 participants from 5 continents and 60 countries. Prevention of disease progression and prediction of future risk, including persistence into adulthood, emerged as the most urgent research questions. Stratified care, based on biomarkers, clinical phenotypes, the children's age, and demographics were also highly rated. The identification of minimum diagnostic criteria in different age groups, cultural perceptions of asthma, and best treatment by age group were priorities for responders from low-middle-income countries. There was good agreement across different stakeholder groups in all domains with some notable exceptions that highlight the importance of involving the whole range of stakeholders in formulation of recommendations. CONCLUSIONS: Different stakeholders agree in the majority of research and strategic (eg, prevention, personalized approach) priorities for pediatric asthma. Stakeholder diversity is crucial for highlighting divergent issues that future guidelines should consider.
Keywords: dospělí; Adult; výzkum; lidé; průzkumy a dotazníky; dítě; Child; Humans; bronchiální astma; Asthma; Surveys and Questionnaires; Research